Literary Competitions Organised by the Ministry of Culture and Arts in 1949–1950 in the Light of Archive Records - Budrowska, Kamila (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The subject of this paper are these literary competitions organized by Ministry of Culture and Arts in the late 1940s and early 1950s. Analysys of the materials from archivesenabled to tackle the issues: these competitions are one of the many aspect of stalinism offensive. Competitions encouraged writers for moving problems of socialist realism, they enforced artists for submission in accordance with Government of country.In article characterized six competitions. Most curious was “Third competition on mass song”, in which took part important writer Tadeusz Różewicz.